Sintesis Surfaktan Non-ionik Berbasis Asam Palmitat Melalui Reaksi Esterifikasi dengan Gliserol - Purbaningdyah, Emma; Sulistyo, Hary; Sediawan, Wahyudi Budi (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2023)
Esterification of glycerol using the fatty acids is one of methods that is widely used in the conversion of glycerol to synthesize products containing monoacylglycerol (MAG) and diacylglycerol (DAG). Among the various types of surfactants, monoacylglycerol (MAG) and diacylglycerol (DAG) are the most widely used of non-ionic surfactants in many industries such as food, pharmacy and cosmetic. This study aims to determine the effect of temperature on the conversion of palmitic acid and the concentration fraction of products. This research was conducted in a batch system with the temperature variations of 80°C, 100°C and 120°C; using 1% HCl catalyst concentration of palmitic acid mass, and reactant mole ratio of 1:1 (glycerol: palmitic acid). Samples were taken every 10 min during 120 min of reaction, to be analyzed by Thin Layer Chromatography (TLC) to determine the concentration fraction of products. The experimental results showed that increasing temperature enhanced the products formation, thus, increased the fraction concentration of products. However, the highest conversion of palmitic acid (80.14%) was obtained at 120°C, with concentration fraction of 1.67% monoacylglycerol (MAG), 10.96% diacylglycerol (DAG) and 6.01% triacylglycerol (TAG).